2019
DOI: 10.1016/j.indcrop.2019.111465
|View full text |Cite
|
Sign up to set email alerts
|

Environmental implications of biohydrogen based energy production from steam reforming of alcoholic waste

Abstract: Nowadays, there is an increasing demand for energy in the world. With an energy system still based on fossil fuels, a paradigm shifts towards clean energy production based on available renewable resources is necessary. Hydrogen is a high-quality energy carrier that can be used with great efficiency and is expected to acquire a great importance in the next generation of fuels. This study aims to analyze the potential environmental impacts associated with the steam reforming of alcoholic waste from distilleries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The environmental impacts of 1 kWh of energy production using sugarcane press-mud were observed as: global warming potential = 1.2 kg CO 2 eq, acidification potential = 0.3 kg SO 2 eq and eutrophication potential = 0.01 kg PO 4 eq Bareiß et al, 2019 The study showed that mainly the composition of the electricity mix determines the impacts like global warming potential for Proton exchange membrane water electrolysis process for hydrogen production. A reduction of the used materials causes only a very little reduction in global warming potential Chen et al, 2019 This study demonstrated that the lowest global warming potential in all the scenarios considered in the integrated supercritical water gasification of coal was 0.66 kg CO 2 eq/kWh Cortés et al, 2019 This study assessed alcoholic waste stream for catalytic steam reforming for the production of hydrogen. The catalyst is composed of a sepiolite base with nickel (15% weight) and lanthanum (1% weight).…”
Section: Key Findings and Recommendations For Future Life Cycle Assessment Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…The environmental impacts of 1 kWh of energy production using sugarcane press-mud were observed as: global warming potential = 1.2 kg CO 2 eq, acidification potential = 0.3 kg SO 2 eq and eutrophication potential = 0.01 kg PO 4 eq Bareiß et al, 2019 The study showed that mainly the composition of the electricity mix determines the impacts like global warming potential for Proton exchange membrane water electrolysis process for hydrogen production. A reduction of the used materials causes only a very little reduction in global warming potential Chen et al, 2019 This study demonstrated that the lowest global warming potential in all the scenarios considered in the integrated supercritical water gasification of coal was 0.66 kg CO 2 eq/kWh Cortés et al, 2019 This study assessed alcoholic waste stream for catalytic steam reforming for the production of hydrogen. The catalyst is composed of a sepiolite base with nickel (15% weight) and lanthanum (1% weight).…”
Section: Key Findings and Recommendations For Future Life Cycle Assessment Studiesmentioning
confidence: 93%
“…Environmental impacts studied in life cycle assessment studies in the context of hydrogen productionEnvironmental impacts ReferenceGlobal warming potentialAlviani Hirano et al 2021, Bareiß De La Rua et al 2019, Booto Aamodt Espegren et al 2021, Bui Zhang et al 2021, Chen Xu et al 2019, Cortés et al 2019, Desantes Molina et al 2020, Fernández-Dacosta Shen et al 2019, Kerscher Stary et al 2021, Kim, Kim et al 2021, Li Liu et al 2019, Li Yao et al 2021, Liu Mauzerall et al 2021, Logan Nelson et al 2020, Ozturk and Dincer 2019, Reaño and Halog 2020, Reaño 2020, Sadeghi Ghandehariun et al 2020, Sako Koyama et al 2021, Sanchez Ruiz et al 2021, Siddiqui and Dincer 2019, Valente Iribarren et al 2019 Net energy use, depletion of fossil fuelsAlviani Hirano et al 2021, Bui Zhang et al 2021, Cortés et al 2019, Cvetković et al, 2021, Kim, Kim et al 2021, Reaño 2020, Sanchez Ruiz et al 2021, Fernández-Dacosta Shen et al 2019, Li Liu et al 2019, Ozturk and Dincer 2019, Siddiqui and Dincer 2019, Valente Iribarren et al 2019 Abiotic depletion potential Booto Aamodt Espegren et al 2021, Chen Xu et al 2019, Karaca Dincer et al 2020, Kim, Kim et al 2021, Ozturk and Dincer 2019, Sako Koyama et al 2021, Sanchez Ruiz et al 2021 Acidification potential Booto Aamodt Espegren et al 2021, Chen Xu et al 2019, Cortés et al 2019, Karaca Dincer et al 2020, Kim, Kim et al 2021, Li Yao et al 2021, Reaño 2020, Sanchez Ruiz et al 2021, Ozturk and Dincer 2019, Siddiqui and Dincer 2019, Valente Iribarren et al 2019 Eutrophication potential Booto Aamodt Espegren et al 2021, Chen Xu et al 2019, Cortés et al 2019, Kim, Kim et al 2021, Li Yao et al 2021, Reaño 2020, Sanchez Ruiz et al 2021, Ozturk and Dincer 2019, Siddiqui and Dincer 2019 Ozone layer depletion potential Booto Aamodt Espegren et al 2021, Bareiß De La Rua et al 2019, Chen Xu et al 2019, Cortés et al 2019, Karaca Dincer et al 2020, Ozturk and Dincer 2019 Photochemical oxidant formation potential Booto Aamodt Espegren et al 2021, Bareiß De La Rua et al 2019, Chen Xu et al 2019, Cortés et al 2019, Ozturk and Dincer 2019, Siddiqui and Dincer 2019 Metal depletion potential Bareiß De La Rua et al 2019 Particulate matter formation potential Bareiß De La Rua et al 2019, Cortés et al 2019, Siddiqui and Dincer 2019 Land use Ozturk and Dincer 2019 Terrestrial ecotoxicity potential Bareiß De La Rua et al 2019, Cortés et al 2019, Ozturk and Dincer 2019, Reaño 2020 Freshwater ecotoxicity potential Cortés et al 2019, Ozturk and Dincer 2019, Sanchez Ruiz et al 2021 Marine ecotoxicity potential Cortés et al 2019, Ozturk and Dincer 2019 Human toxicity potential Booto Aamodt Espegren et, Bareiß De La Rua et al 2019, Chen Xu et al 2019, Cortés et al 2019, Karaca Dincer et al 2020, Ozturk and Dincer 2019, Sanchez Ruiz et al 2021, Siddiqui and Dincer 2019 …”
mentioning
confidence: 99%
“…Even higher benefits could be observed if considering as counterfactual other waste management practises, such as landfill or incineration with no energy recovery. There are currently several studies in literature on the production of hydrogen from first-and second-generation biomass as feedstock source (Bhatia et al, 2021;Cortés et al, 2019;Susmozas et al, 2016;Tian et al, 2019). However, the production of Bio-H2, either from biomass or waste feedstock, would still need to be proven at a commercial scale to validate the model assumptions.…”
Section: Bio-h2 Climate Change Contribution and Counterfactual Casementioning
confidence: 99%
“…Hydrogen, with its renewable, safe, high-quality energy density and environmentally friendly properties, has emerged as the top alternative to fossil fuels [1][2][3]. In contrast to other methods such as steam methane reforming, biomass and coal gasification for hydrogen production, water splitting for hydrogen production stands out as the most extensively adopted and developed method, especially known for its straightforward and non-polluting process [4][5][6].…”
Section: Introductionmentioning
confidence: 99%